REGENERATION OF DRY DEBRIS-CONTAMINATED LUBRICATION - T. A. Ahmetov; O. I. Ignatenko; D. G. Sachava (Литьë и металлургия)
Industrial testing of regenerated lubricant in the process of wire drawing showed satisfactory quality (absence of gloss). It is determined that consumption of regenerated lubricant does not differ from consumption of new lubricant. Regenerated lubricant corresponds to the requirements of normative documents.